Influence of the injection molding process on the tooth deflection of plastic gears during operation - Herzog, Christoph; Drummer, Dietmar (VDI Verlag GMBH, 2023)
A new test methodology for in situ deformation and wear measurement of plastic gears has been developed at the Institute of Polymer Technology (LKT). The in situ gear test rig evaluates the time differences between successive index pulses from encoders on the input and output shafts. This measuring principle enables continuous measurement of elastic tooth deformation and the combination of plastic tooth deformation and flank wear by alternating between a high loading torque and a lower measuring torque. The newly developed measurement principle was used to investigate the influence of manufacturing-related geometrical and morphological deviations on elastic tooth deflection. The results show that an increased degree of crystallinity is associated with lower tooth deflections. Tool-related shape deviations, on the other hand, barely influence the deformation behavior. The design of the shaft-hub connection of the plastic gear, however, significantly influences the measured angular displacement between input and output shaft.
CRIS-Team Scopus Importer:2024-12-16